The Effect Of Employee Engagement And Organizational Citizenship Behavior On The Performance Of Employees Of The Research & Development And Education & Training Agency Of The Ministry Of Religion Of The Republic Of Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The management of human resources at the Secretariat of the Research and Development and Training Agency (a public organization that is identical to religious values) experiences problems because the importance of employee performance, employee engagement, and organizational behaviour are still below 75. This study aims to determine whether employee engagement and organizational citizenship behaviour positively and significantly impact employee performance. This research finds that employee engagement has a positive and significant impact on employee performance, while organizational citizenship behaviour has a negative and insignificant impact on employee performance. This research supports previous research, which states that employee engagement positively and significantly impacts employee performance. However, this research refutes previous research applied to private organizations, which states that organizational citizenship behaviour has a significant positive impact on employee performance.